2018
DOI: 10.1107/s2053230x18008543
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and kinetic analyses ofN-acetylmannosamine-6-phosphate 2-epimerases fromFusobacterium nucleatumandVibrio cholerae

Abstract: Sialic acids are nine-carbon sugars that are found abundantly on the cell surfaces of mammals as glycoprotein or glycolipid complexes. Several Gram-negative and Gram-positive bacteria have the ability to scavenge and catabolize sialic acids to use as a carbon source. This gives them an advantage in colonizing sialic acid-rich environments. The genes of the sialic acid catabolic pathway are generally present as the operon nanAKE. The third gene in the operon encodes the enzyme N-acetylmannosamine-6-phosphate 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…F. nucleatum is not known to express sialidase of its own [41], but it commonly resides among sialidase-producing bacteria in the mouth, gut, and vagina [42][43][44][45][46]. Some F. nucleatum strains also encode putative sialic acid catabolic pathways, although functional characterization of the corresponding gene products is still limited [47][48][49][50][51]. We hypothesized that F. nucleatum may derive nutritional benefit from host sialoglycans when exogenous sialidases produced by other bacteria are present.…”
Section: Introductionmentioning
confidence: 99%
“…F. nucleatum is not known to express sialidase of its own [41], but it commonly resides among sialidase-producing bacteria in the mouth, gut, and vagina [42][43][44][45][46]. Some F. nucleatum strains also encode putative sialic acid catabolic pathways, although functional characterization of the corresponding gene products is still limited [47][48][49][50][51]. We hypothesized that F. nucleatum may derive nutritional benefit from host sialoglycans when exogenous sialidases produced by other bacteria are present.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is not known whether F. nucleatum benefits from or contributes to the growth of other organisms in the dysbiotic vaginal microbiome. We note that although some F. nucleatum strains seem to encode a sialic acid catabolic pathway (Caing-Carlsson et al, 2017;Gangi Setty et al, 2014;Manjunath et al, 2018;Yoneda et al, 2014), F. nucleatum is not known to express sialidases (Moncla et al, 1990). Thus, we wondered whether F. nucleatum might obtain sialic acids liberated by sialidases produced by other bacteria.…”
Section: Introductionmentioning
confidence: 94%
“…Some bacteria can import free sialic acids from the extracellular compartment via a sialic acid transporter (SiaT) and then use a sialate lyase (NanA) to convert them to Nacetyl-mannosamine (ManNAc) and phosphoenolpyruvate (Haines-Menges et al, 2015;Severi et al, 2007;Vimr and Troy, 1985). Recent studies suggest that at least some strains of F. nucleatum encode these functionalities (Gangi Setty et al, 2014;Manjunath et al, 2018;Yoneda et al, 2014). Our bioinformatic analysis of 28 F. nucleatum proteomes revealed that about half of the sequenced strains encoded a putative NanA (Figure S1).…”
Section: F Nucleatum Catabolizes Free Sialic Acidmentioning
confidence: 99%
“…[204] (I) N-Acetylmannosamine6-phosphate(NMan6P,blue) and N-acetyl-d-glucosamine 6-phosphate (NGlu6P, green)a sb ound to NanE from Vibrio cholerae (PDB 5ZJN and 5ZJP,respectively) are shown. [205] (J) GDP-a-d-mannose (GDP-Man, blue) and GDP-b-l-galactose (GDP-Gal, green) as bound to the K217Aa nd Y174F variants of GME from A. thaliana,respectively,(PDB 2C5E and 2C5A,r espectively) are shown. [206] (K) GDP-a-d-mannose (GDP-Man, blue)a nd GDP-b-l-galactose (GDP-Gal, green) as bound to GME from Arabidopsis thaliana (PDB 2C59)a re shown.…”
Section: D-psicose 3-epimerase( Dpe)mentioning
confidence: 99%
“…[204,230] The X-ray crystal structures of NanE from Vibrio cholera with bound ManNAc-6-P( PDB 5ZJN) and bound GluNAc-6-P (PDB 5ZJP) were solved by modelling either ligand into the same data set to obtain final structures of the two complexes. [205] In both structures, the substrate and the product are bound as their open-chain forms, and most of the interactions with the protein are the same forb oth ligands. Superposition of the structures of the bound epimers( Figure 3H) reveals that the phosphate oxygens are held in place by Hbondsw ith the backbone amide nitrogen atoms of Gly209, Arg188, and Ser210.H -Bonding interactions between the sugar O3 and O4 atoms and the side chain of Arg214, as well as an H-bondb etween O5 and the side chain of Glu186,h old the C3-C6 atoms in ar oughly linear arrangementw iths eparations of 0.60 between the correspondinga toms of each ligand.…”
Section: N-acetylmannosamine 6-phosphate 2-epimerase (Nane)mentioning
confidence: 99%